A bibliometric analysis of recycled concrete research (1978–2019). Issue 5 (2nd September 2020) - Oshodi, Olalekan Shamsideen; Awuzie, Bankole Osita; Akotia, Julius; Ademiloye, Adesola S.; Ngowi, Alfred
Abstract : Purpose: The use of recycled concrete (RC) can reduce the greenhouse emissions associated with the production of cement, which is one of the primary materials used for the execution of construction projects. This research aims to review the state of knowledge in the field of RC research. An understanding of the state of the art in the RC domain justifies future research in this field. Design/methodology/approach: A systematic and comprehensive search of RC-related literature was conducted using the Scopus database. In this research, the bibliometrix R-package was used for the analysis of bibliometric information of the selected papers. The software was used to create a map, which highlights the trends and gaps in the RC knowledge domain. Findings: The results reveal the research themes, clusters, collaboration networks and advancement of knowledge in the field of RC research. The study integrates the literature focussed on RC research and provides a platform for progression of knowledge in this field. Originality/value: The study contributes to the growing body of knowledge by providing an up-to-date RC knowledge map based on an analysis of bibliographic data. Information gleaned from previous studies suggests that bibliometric review can strengthen and complement the findings emerging from other forms of literature reviews. The study reported here is one of the first studies to provide insights into the evolution of RC research.